Penile Implant Infection: Experience With Expanded Salvage Criteria and a Shortened Course of Postoperative Antibiotics. Issue 3 (9th June 2020) - Chandrapal, Jason; Harper, Shelby; Davis, Leah G.; Lentz, Aaron C.
Abstract: Introduction: The preferred treatment for inflatable penile prosthesis (IPP) infection includes antibiotic therapy, device removal, and immediate replacement. While this is an accepted procedure, the delivery and length of postoperative antibiotics are not standardized. Furthermore, historical salvage criteria may be overly restrictive given the new salvage techniques. Aim: Our aim is to determine if an expanded salvage criteria and shorter course of antibiotics demonstrate acceptable IPP infection rates. Methods: We retrospectively reviewed 466 consecutive IPP cases from a single surgeon between March 2014 and March 2019. Salvage and reinfection were determined by current procedural terminology codes, and the final cohort was individually reviewed for integrity. Demographic, operative, and culture data from each patient were obtained. All patients were discharged on oral antibiotics after initial salvage. Patients were not excluded for exposed hardware, immunosuppression, tissue necrosis, severe diabetes, or corporal purulence. Owing to the small sample size, only descriptive statistics were used to describe the final cohort. Main Outcome Measures: The main outcome measures were classification of microorganisms cultured at the time of salvage and salvage failure rate. Results: A total of 26 cases of IPP infections (6%) were identified. The median (interquartile ratio) age and body mass index were 62 (58–66) and 32 (28–34), respectively. During initial salvage, gross purulence was noted in 9 patients (35%), and 22 patients (84%) had a malleable prosthesis placed. The most prescribed postoperative antibiotic was Bactrim/Augmentin with a median (interquartile ratio) antibiotic duration of 14 days (11–14). After IPP salvage, 2 patients (8%) developed a reinfection while on oral antibiotics. One of those patients was immunosuppressed, and the other was infected with Candida glabrata . Conclusion: Expanded salvage criteria and postoperative oral antibiotic duration of at least 14 days demonstrated an acceptable infection rate. This suggests that a longer antibiotic therapy may not be necessary.